Jahrbuch der Juristischen Zeitgeschichte (De Gruyter, 2010)
The Jahrbuch der Juristischen Zeitgeschichte first appeared in the year 2000. Alongside original articles, it features reprints of materials otherwise difficult to access by many professionals with an interest in contemporary legal history, as well as conference reports and organizational reports from participating institutions within this field. The journal is of particular interest to legal historians as well as practicing lawyers.